Analysis of Indonesia's Response to the Russia-Ukraine Conflict in 2022 - Oktadhio, I Gusti Ngurah Divandra Prema; Wiranata, I Made Anom (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 4 No 4 (2025): JURNAL DIKSHI, 2025)
The outbreak of the conflict between Russia and Ukraine gave rise to various responses in international circles due to the impacts resulting from the conflict, such as the large number of casualties and the emergence of threats to food security. This incident then prompted the UN General Assembly forming a special session to discuss the conflict between Russia and Ukraine. Then from the trial it was discovered that the majority of them chose to criticize Russia because they were seen as the cause of the conflict. However, there are still several countries that choose to be impartial, including Indonesia. Looking at Indonesia's response, this research seeks to find out why Indonesia gave a impartial response to the Russia-Ukraine conflict. This research applies qualitative research methods with secondary sources which are then analyzed using the concepts of Prudent Judgment Approach and Hedging Strategy. From this analysis, it is known that the reason why Indonesia took a cautious and impartial response towards this conflict was due to the conditions of uncertainty and ambiguity of the threat felt by Indonesia. Therefore, Indonesia needs to be careful in further analyzing the right strategy for Indonesia to be able to avoid these uncertain conditions and impartial response as an effort for Indonesia to maintain good relations with the parties in conflict.